Essays in law and finance - Austin, N (2023)
This dissertation consists of three essays in law and finance, with applications in private markets and real estate. In the first chapter, I examine the direct impacts of concentrated ownership by private market funds. Using the hotel industry as a laboratory, I show that private funds and REITs use the opacity of their ownership structures to purchase seemingly competing hotels within the same market. I show that increased concentration of ownership by private markets funds following acquisitions that cause exogenous shocks to ownership concentration results in decreased customer satisfaction (especially perceptions of value and service) according to reviews from TripAdvisor.com.